2013
DOI: 10.1128/jvi.02761-12
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Phosphorylation of Phosphoprotein of Vesicular Stomatitis Virus Is Required for Preventing Nucleoprotein from Binding to Cellular RNAs and for Functional Template Formation

Abstract: bThe phosphoprotein (P) of vesicular stomatitis virus (VSV) plays essential roles in viral RNA synthesis. It associates with nascent nucleoprotein (N) to form N 0 -P (free of RNAs), thereby preventing the N from binding to cellular RNAs and maintaining the N in a viral genomic RNA encapsidation-competent form for transcription and replication. The contributions of phosphorylation of P to transcription and replication have been studied intensively, but a concrete mechanism of action still remains unclear. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…This complex is essential to prevent premature N oligomerization rather than to prevent RNA binding. This concept is supported by results reported by Chen et al, who showed that a phosphorylation-deficient triple mutant of P (P3A) that is mutated outside the cavity binding region could not prevent encapsidation of cellular RNA by VSVN (37).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This complex is essential to prevent premature N oligomerization rather than to prevent RNA binding. This concept is supported by results reported by Chen et al, who showed that a phosphorylation-deficient triple mutant of P (P3A) that is mutated outside the cavity binding region could not prevent encapsidation of cellular RNA by VSVN (37).…”
Section: Resultssupporting
confidence: 79%
“…The N terminus of P interacts with the back of the C-terminal half (C-lobe) of N. An ␣-helix corresponding to residues 17 to 31 of P was shown to occupy the RNA cavity in the structure. Subsequent studies by Chen et al (37), using a P3A mutant (triple mutations of Ser or Thr to Ala), showed that phosphorylation of P at Ser60, Thr62, and Ser64 is required to prevent N 0 from encapsidating cellular RNA, which leads to a dead-end product of N and diminishes viral replication. In the SAXS model, Ser60, Thr62, and Ser64 were notably positioned to form charge interactions with Lys398, Arg399, Lys414, and Lys417 of N (here named the "PO binding site").…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that the CAT expression in the VSV miningenome system was regulated by both transcription and replication; that is, defects in either transcription or replication result in the loss of CAT expression (Chen et al, 2013). Having observed that N TVK4-6A3 , N RII7-9A3 , N VIV13-15A3, and N R7A did not support CAT expression, we next sought to determine whether these mutants are transcription or replication defective or both in RNA synthesis by real-time RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we assumed that these mutants had an effect on both transcription and replication, to greater degree on transcription. Because replication defects also influence transcription, and to confirm that transcription is also defective independent of effect of replication, we used a replication-deficient VSV minigenome (ΔTr minigenome) (Chen et al, 2013), and we repeated the aforementioned experiment using the same mutants. The results showed that the CAT expression levels supported by N TVK4-6A3 , N RII7-9A3 , N VIV13-15A3, and N R7A were 10% less than the levels supported by N wt (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation